Revisiting Incapacitation: Can We Generate New Estimates? - Reuter, Peter (Journal of quantitative criminology, 2007)
A substantial body of empirical research examines how the huge expansion in incarceration in the United States since the early 1970s has influenced crime. These studies merge the effects of three conceptually distinct paths by which incarceration might reduce crime: general deterrence, specific deterrence and incapacitation. This issue of the Journal focuses specifically on the incapacitation path. This Introduction reviews the individual papers and offers the editors’ judgment as to the plausibility of progress using different research strategies. It emphasizes the potential for using individual level data to take advantage of natural experiments.